Research of Measuring and Control Technology of Shipborne Satellite Antenna Auto-Tracking System - Wang, Xi Kun (Applied Mechanics and Materials, 2014)
Mobile carrier satellite communications are becoming increasingly attention. Civil, with satellite television, satellite Internet access, as well as development of civilian systems such as video phones, on growing demand for mobile communications carrier; the military, rapid response to equipment and mobility as well as steady aim, track and combat capabilities of mobile high demand, also depend on the mobile carrier satellite communications. Mobile carrier satellite communications system is the key equipment of satellite antenna auto-tracking system. Develop performance-price ratio reasonable automatic satellite antenna tracking system to fill the gaps in this area, is of great significance.